Cultivating official culture through visual communication: stamp design in the republic of Cyprus, perceptions of citizens and ideology - Andreou, Sonia (Τμήμα Πολυμέσων και Γραφικών Τεχνών, Σχολή Καλών και Εφαρμοσμένων Τεχνών, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Postage stamps play a significant role in the establishment of a country’s image, as they carry a variety of meanings through their visual representations. They are artefacts of national identity, since they are simultaneously defined by the official culture of a nation, and can be considered ‘visual ambassadors’ of the country they represent. These images address and transfer messages to both internal and external audiences, serving a role that remains of outmost importance for stamp-designing programs. The particular purpose of stamp imagery however, has not been empirically researched and therefore created an issue for consideration. The inclusion of the citizen’s perspective (internal audiences) aside from introducing a new approach in researching the particular subject, was required in order to substantially explore how ideological meanings are constructed through stamp design, since these everyday objects contribute to the shaping of collectiveness within a state. The country which the study concentrates on is the Republic of Cyprus, a relatively ‘young’ post-colonial state, founded in 1960. A mixed methods design was adopted for the particular dissertation in order to aid us in studying not only the messages sent by the government through stamp design, but also the perceptions of citizens. The dissertation involves three stages that took place sequentially, while their findings informed each other. The first study employed quantitative content analysis in order to investigate through a sample of 998 postage stamps issued by the Republic of Cyprus, the predominant themes appearing in this corpus, and the messages they carried as defined by the official culture. The second study built on these findings and explored the views and preferences of 384 Cypriot citizens in relation to their country’s official representation as depicted on stamp imagery, through a survey research. The final study was designed following the need to gain in-depth information and understanding of the citizens’ perceptions, as these emerged from our previous findings. Following this rationale, for the last part we chose to conduct focus group interviews with 20 Cypriot citizens who have already participated in the second study. Our findings revealed the need for an ideologically inclusive repertoire coming from both the existing official culture, as well as the citizens, expressed in different manners. We demonstrated how the government and citizens are in search of a renewed approach to the Republic of Cyprus’ image-construction, through the semiotics of stamps; one that highlights their local cultural identity, respects older forms of representation, and is simultaneously independent from vii that of any other country. Concluding, this dissertation proved how postage stamps as subtle carriers of ideological messages can cultivate and influence the official culture, as well as the views of the citizens. We have additionally shown how the citizens do not necessarily accept and adopt all of these messages, mediating and modifying them in order to reflect their own views, positions and experiences. It can be therefore observed that the perceptions deriving both from the government’s decisions and from the citizens can get altered over time, and are particularly susceptible to the ever-changing historical, political and social differentiations that take place. In this sense, we argue that studies such as the one presented contribute to the uncovering of various aspects of the societies in question, as well as their citizens and their decision-making centres, as they go through important changes. The dissertation concludes with suggestions for future research regarding the role of the citizen and the implications for the authorities regulating stamp-designing programs, national collectiveness through visual communication, the designers themselves, as well as educators.
Keywords: Postage stamps; Visual communication; Official culture; Citizens; Republic of Cyprus